Zielonogórskie muzealnictwo winiarskie w latach 1922-2017 = The wine collections and exhibitions in Zielona Góra from 1922 to 2017 - Cincio, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the development of the collections and the exhibitions related to the viticulture in Zielona Góra. The first museum collections documenting the history of the winemaking in Zielona Góra and the region were created before the First World War. Their development was related to technological progress and a gradual decrease in crop area. These collections are systematically developed, mainly by the Museum of the Lubusz Region in Zielona Góra.
Keywords: muzeum; muzealogia; winiarstwo; historia; museum; museology; wine heritage; history